Effects of local permitting and interconnection requirements on solar PV installation durations. (February 2022) - O'Shaughnessy, Eric; Dong, Shiyuan; Cook, Jeffrey J.; Cruce, Jesse; Ardani, Kristen; Fekete, Emily; Margolis, Robert
Abstract: Most rooftop solar photovoltaic (PV) systems must be reviewed and approved by local governments and electric service providers prior to operation. These permitting, inspection, and interconnection (PII) requirements help ensure safe PV system installation and operation, but onerous requirements may needlessly delay construction and operation. Here, we analyze PV PII data to understand the effects of local PII requirements on PV process durations. We combine data on local PII requirements with estimates of process durations for 248, 741 PV systems installed in the United States. The data show that local variations in PII requirements can partly explain variations in PV process durations. Requirements that would be expected to reduce durations—such as instant online approvals—are generally associated with shorter durations, while requirements that would be expected to increase durations—such as structural reviews—are associated with longer durations. We find only weak evidence that measures to expedite pre-install processes result in post-install delays, and similarly find only weak evidence that increased pre-install PII oversight can save time in post-install stages. Our results provide further rationale for PII authorities to analyze their requirements and identify opportunities to streamline PII processes. Highlights: Study of rooftop solar permitting, inspection, and interconnection (PII) requirements. PII varies significantly across jurisdictions. PII differences partly explain differences in solar installation timelines. Expedited PII requirements yield shorter installation timelines. Results suggest that PII reforms could reduce solar installation timelines.